2019
DOI: 10.12998/wjcc.v7.i11.1262
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of interleukin-1β, interleukin-6, tumor necrosis factor-α and vascular endothelial growth factor in patients with knee articular cartilage injury

Abstract: BACKGROUND Inflammatory cytokines play a vital role in the occurrence of osteoarticular injury and inflammation. Whether inflammation-associated factors interleukin-1β (IL-1β), IL-6, tumor necrosis factor-α (TNF-α) and vascular endothelial growth factor (VEGF) are involved in the pathogenesis of keen articular cartilage injury remains poorly understood. AIM To measure the levels of inflammatory factors [IL-1β, IL-6, TNF-α and VEGF] in patients with knee articular cartil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 21 publications
(16 reference statements)
0
17
0
2
Order By: Relevance
“…The macrophage phenotype accumulates and localizes after articular cartilage injury. Macrophages, fibroblasts and chondrocytes secrete increased inflammatory factors, including interleukin‐1ß( IL‐1ß ), IL‐6 , IL‐8 , IL‐17 , IL‐18 , tumor necrosis factor‐ɑ ( TNF‐ɑ ), etc 86,87 . These inflammatory factors can directly or indirectly activate some signaling pathways related to angiogenesis, such as STAT3 , NF‐κB , PI3K/Akt , and p38 MAPK .…”
Section: Regulatory Factors Of Angiogenesis In Acmentioning
confidence: 99%
“…The macrophage phenotype accumulates and localizes after articular cartilage injury. Macrophages, fibroblasts and chondrocytes secrete increased inflammatory factors, including interleukin‐1ß( IL‐1ß ), IL‐6 , IL‐8 , IL‐17 , IL‐18 , tumor necrosis factor‐ɑ ( TNF‐ɑ ), etc 86,87 . These inflammatory factors can directly or indirectly activate some signaling pathways related to angiogenesis, such as STAT3 , NF‐κB , PI3K/Akt , and p38 MAPK .…”
Section: Regulatory Factors Of Angiogenesis In Acmentioning
confidence: 99%
“…Moreover, a high innate capacity to produce IL-6, in response to lipopolysaccharide stimulation, was associated with hand OA development in 90-year-old individuals [ 45 ]. Higher IL-6 levels in OA serum or SF also correlate with disease progression or severity of cartilage pathology [ 42 , 46–48 ]. This suggests that IL-6 levels may reflect cartilage damage, which is supported by the fact that SF IL-6 levels are strongly increased in individuals with cartilage defects but no macroscopic signs of OA [ 49 , 50 ].…”
Section: Local and Systemic Perspective: Levels Of Il-6 And Its Solubmentioning
confidence: 99%
“…The onset of defects affects the microenvironment of the whole joint [ 4 , 5 ]. After OCD, an acute inflammatory response occurs in the joint [ 6 , 7 ]. Previous studies have identified the overexpression of interleukin-1β (IL-1β) in the surrounding tissues of the defect [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…After OCD, an acute inflammatory response occurs in the joint [ 6 , 7 ]. Previous studies have identified the overexpression of interleukin-1β (IL-1β) in the surrounding tissues of the defect [ 8 , 9 ]. The local inflammatory microenvironment has been proved to be a barrier to osteogenic and chondrogenic differentiation of mesenchymal stem cells (MSCs) [ [10] , [11] , [12] ].…”
Section: Introductionmentioning
confidence: 99%